2022
DOI: 10.1161/strokeaha.121.035640
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Growth and Risk of Adult Cerebrovascular Disease: The NFBC1966

Abstract: Background: Low birth weight is associated with an increased risk of adulthood cerebrovascular disease (CVD). Not much is known about effects of early childhood growth. We studied whether the risk of adult CVD is associated with growth or nutritional factors during early childhood. Methods: Within the Northern Finland Birth Cohort 1966, 11 991 persons were followed from birth to 52 years of age. CVD diagnoses were extracted from national hospital and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…In addition, the pattern of resistin concentrations in serum is due to their higher levels in both metabolic healthy groups without a direct connection with BMI, suggesting a link between visceral obesity and diabetes in these healthy young individuals [ 43 , 44 ]. Therefore, early parameters detected in these populations could be relevant to determining their metabolic status [ 45 ]. However, a pattern of increased serum resistin levels in metabolic diseases has not previously been reported [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the pattern of resistin concentrations in serum is due to their higher levels in both metabolic healthy groups without a direct connection with BMI, suggesting a link between visceral obesity and diabetes in these healthy young individuals [ 43 , 44 ]. Therefore, early parameters detected in these populations could be relevant to determining their metabolic status [ 45 ]. However, a pattern of increased serum resistin levels in metabolic diseases has not previously been reported [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Stroke , Mikkola et al 1 report on data from the prospective Northern Finland Birth Cohort 1966 study to determine the effect of body mass index (BMI) and its changes in adolescence and young adulthood (measured at ages 14 and 31 years) on ischemic and hemorrhagic stroke occurring in young adulthood (ie, between ages 14 and 54 years). They found that the risks of ischemic stroke were associated with both overweight and obesity in younger women but not in men.…”
mentioning
confidence: 99%
“…13 The E-values calculated by Mikkola et al were low to moderate, indicating that little unmeasured confounding would be needed to explain the effect estimates. 1 Assessment of obesity/overweight relies on BMIs. The waist-to-hip ratio reflecting abdominal obesity is a stronger risk factor for stroke compared with BMI and has an even greater effect in young adults.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the Northern Finland Birth Cohort 1966, previous research has established that low early childhood weight and height increase the risk of ischemic cerebrovascular disease in adulthood among women, and the timing of weight gain during childhood plays a significant role in the development of cerebrovascular disease risk among women. 12 Sex disparity in cerebrovascular disease occurrence has been well identified. The age-adjusted incidence of cerebrovascular disease is higher in men than in women, except in the elderly, which is mostly a result of longer life expectancies in women.…”
mentioning
confidence: 99%